Evaluation of Performance of Enterprise Development Strategy Implementation - FURSOV, Victor Alexandrovich; LAZAREVA, Natalia Vyacheslavovna; SOLOVIEVA, Irina Vasilievna; FATTAKHOVA, Alfiya Ruslanovna; VASLAVSKAYA, Irina Yrevna (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
Performance indicators of the enterprise strategy from a theoretical point of view and their application in the activities of economic entities were considered. The technique of multidimensional comparative performance evaluation of the enterprise strategy was founded; the more specific elements of the evaluation were suggested. The main advantage of the method is the ability to choose an adequate development strategy. The importance of the implementation of the efficient enterprise strategy at the macroeconomic level as a pledge of successful social and economic development of territories was presented.
Keywords: strategy; strategic alternative; strategic plan; performance indicators; multidimensional comparative evaluation